Logistic Supply Chain Management System Modeling Using Blockchain - Solihin, Muhammad Alif; Nur, Dahliah; Tungadi, Eddy; Yusri, Iin Karmila (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
Indonesia's economic growth in the logistics sector is becoming increasingly significant, alongside the rising demand for goods. However, the complexity of logistics supply chain management in Indonesia still faces challenges, including security, human error, and lack of transparency. This research proposes the use of blockchain technology for a logistics supply chain management system, which is capable of storing transaction data in a decentralized and distributed manner. Ganache is used as a local blockchain server, Metamask for transactions, and smart contracts to manage user flows on a web3 dapps-based website. The research procedure includes literature study, design, development, and system testing. The test results indicate that all features and functions of the system operate as expected. The system not only successfully handles high demand and transaction spikes but also demonstrates enhanced data security, improved transparency through real-time tracking, and robust performance under high workloads. Overall, this blockchain-based logistics supply chain management system effectively secures and manages transaction data while enabling data tracking and tracing, thereby increasing transparency and handling high concurrent transactions efficiently.